LEXICAL COMPATIBILITY OF DESTRUCTIVE VERBS OF THE TURKISH LANGUAGES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article describes the lexical compatibility, valence possibilities and associative relations in destructive verbs of action in the Turkic languages. The issues of studying destructive verbs of action in the comparative-historical aspect within the framework of the vocabulary of the Turkic languages, in particular, the Uzbek, Karakalpak, Turkmen languages, are covered. At the same time, the lexical compatibility of such destructive verbs of action as buzmoq - buzıw – bozmak (destroy), sindirmoq – búldiriw – dowmek (break) within the text (mainly on the example of folk proverbs) is analyzed.